THE EFFECT OF E-LEARNING TOWARD STUDENTS LEARNING INTEREST AT PANDEMIC COVID’19 ERA IN RURAL AREA - Wahyuni, Rina; Utami, Surti Nur (SIGEH ELT : Journal of Literature and Linguistics, 2022)
Tehnology has played as a significant role in teaching and learning. As an aspect of technology,E-learning has been believed to be an effective learning media of higher educational in institution.Pandemic Covid’19 is really having huge impact for people around the world unexpected ineducational field. In this era, the activity of teaching and learning process was changed to be anonline term. Thus, the objective of this research is to explore the effect of E learning towardstudents learning interest in Covid’19 era especially in rural area. The researcher conducted inAkademi Kebidanan Wahana Husada Bandar Jaya Central Lampung. The population of thisresearch is the students in AKBID Wahana Husada Bandar Jaya at the first semester in academicyear 2020/2021. The data collecting technique is using questionnaire, and to analysis the data, theresearcher used T-test. The finding of this research, the students more interest to join the classmeeting by E-learning. It saw by their result in fulfill the questionnaire. The result showed that Elearning is having positive effect toward students learning interest in Covid’19 era. The studentsfelt enjoy with this kind of learning.